Antithrombin III “Northwick Park”: A Variant Antithrombin with Normal Affinity for Heparin but Reduced Heparin Cofactor Activity - Howarth, D J; Samson, Diana; Stirling, Yvonne; Seghatchian, M J (Thrombosis and Haemostasis, 1985)
Further studies have been carried out in a previously reported family with congenital antithrombin III (AT III) deficiency due to an abnormal variant of AT III (AT III Northwick Park). The variant has been identified in five members of the family, three of whom had a history of venous thrombosis. Inheritance followed an autosomal dominant pattern. The affected family members have reduced levels of antithrombin heparin cofactor (41–67%) and progressive antithrombin activity (44–62%) but normal levels of immunoreactive AT III (91–162%). Two dimensional immunoelectrophoresis (2 DIE) of AT III in the absence of heparin revealed an abnormal fast-moving peak in addition to the normal peak but 2 DIE in the presence of heparin appeared normal. Further studies confirmed that the abnormal AT III binds completely to heparin but has no heparin cofactor or progressive antithrombin activity. These results would be consistent with a mutation affecting the binding site for thrombin.
Keywords: Antithrombin III; Thrombin; Heparin cofactor